2006
DOI: 10.1021/ma060920n
|View full text |Cite
|
Sign up to set email alerts
|

Field-Driven Translocation of Regular Block Copolymers through a Selective Liquid−Liquid Interface

Abstract: We propose a simple scaling theory describing the variation of the mean first passage time (MFPT) τ (N, M ) of a regular block copolymer of chain length N and block size M which is dragged through a selective liquid-liquid interface by an external field B. The theory predicts a non-Arrhenian τ vs. B relationship which depends strongly on the size of the blocks, M , and rather weakly on the total polymer length, N . The overall behavior is strongly influenced by the degree of selectivity between the two solvent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] For a polymer threading through a nanopore, loss of available configurations due to the geometric constriction leads to an effective entropic barrier. Kasianowicz et al 7 demonstrated that an electric field can drive single-stranded DNA and RNA molecules through the water-filled ␣-hemolysin channel and that the passage of each molecule is signaled by a blockade in the channel current.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] For a polymer threading through a nanopore, loss of available configurations due to the geometric constriction leads to an effective entropic barrier. Kasianowicz et al 7 demonstrated that an electric field can drive single-stranded DNA and RNA molecules through the water-filled ␣-hemolysin channel and that the passage of each molecule is signaled by a blockade in the channel current.…”
Section: Introductionmentioning
confidence: 99%
“…23,26,28,31 This has been indicated to be inappropriate for the study of translocation dynamics. [38][39][40][41][42][43][44] Most recently, we have investigated both free and forced translocation using both the two-dimensional fluctuating bond model with single-segment Monte Carlo moves 42,43 and Langevin dynamic simulations. 44,45 For the free translocation, 42,44 we numerically verified that the translocation time ϳ N 1+2 , where N is the chain length and is the Flory exponent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) and b 0 is given in Eq. (19). Therefore, constant A is determined by all of the constant transition rates.…”
Section: Expressions For Mean Velocity and Effective Diffusion Cmentioning
confidence: 99%
“…Explicit expressions for a k s and a k s can also be obtained via Eqs. (15,18,19,23,25). Next, we begin to derive the expressions for T k s and T k s. In the stationary-state limit (see Eqs.…”
Section: Expressions For Mean Velocity and Effective Diffusion Cmentioning
confidence: 99%